(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Information about amino acids synthesized by plants, their functions in amino acid metabolism, the pharmacological activity of some of them, especially in the formation of hepatoprotective factors of the body’s defense in liver diseases, is generalized. This article presents the amino acid composition of dry extracts of plant seeds grown in the environment of Uzbekistan, describes the analytical results obtained using the HPLC (High Performance Liquid Chromatography) method, and their conclusions. The object of the study was the fruits of the milk thistle [Silybum marianum (L.) Gaertn.]